More than ramps a guide to improving health care quality and access for people with disabilities - Iezzoni, Lisa I.; O'Day, Bonnie (New York ; Oxford : Oxford University Press, 2006)
Many Americans live with some sort of disability and this book in three parts looks initially at the historical roots of healthcare access for those with disabilites. The second part discusses the current situation and the final part discusses the ways in which healthcare quality and access can improve.
Description based on print version record.
Includes bibliographical references and index.
Keywords: People with disabilities -- Services for -- United States; People with disabilities -- Medical care -- United States; Health insurance -- United States; Patient advocacy -- United States